Freedom of Contract in Sharia Banking for Non-Muslim: Sharia Banking Law Perspective - Ana Laela Fatikhatul Choiriyah; M. Khoidin; Candra Irawan; Yudha Bagus Tunggala Putra (Rechtenstudent, 2025)
Islamic banking in Indonesia has experienced rapid growth as an alternative financial service grounded in justice, transparency, and sharia principles. Interestingly, an increasing number of non-Muslim customers are utilizing Islamic banking products due to their perceived fairness and ethical practices. This phenomenon raises important legal questions, particularly regarding the validity and legal certainty of contracts involving non-Muslim customers from the perspective of fiqh muamalah. The principle of freedom of contract in Islamic law allows for contractual agreements with anyone, as long as the content and structure do not contradict sharia principles. This study aims to examine the legal validity, certainty, and practical application of this principle for non-Muslim customers within Islamic banking. By exploring how Islamic financial institutions accommodate inclusivity without compromising core religious values, the research seeks to contribute to the development of a more inclusive and just financial system in Indonesia that respects both religious norms and pluralistic societal realities.